The Role of Glutamine and Glutaminase in Pulmonary Hypertension - Wang, Shang; Yan, Yi; Xu, Wei-Jie; Gong, Su-Gang; Zhong, Xiu-Jun; An, Qin-Yan; Zhao, Ya-Lin; Liu, Jin-Ming; Wang, Lan; Yuan, Ping; Jiang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary hypertension (PH) refers to a clinical and pathophysiological syndrome in which pulmonary vascular resistance and pulmonary arterial pressure are increased due to structural or functional changes in pulmonary vasculature caused by a variety of etiologies and different pathogenic mechanisms. It is followed by the development of right heart failure and even death. In recent years, most studies have found that PH and cancer shared a complex common pathological metabolic disturbance, such as the shift from oxidative phosphorylation to glycolysis. During the shifting process, there is an upregulation of glutamine decomposition driven by glutaminase. However, the relationship between PH and glutamine hydrolysis, especially by glutaminase is yet unclear. This review aims to explore the special linking among glutamine hydrolysis, glutaminase and PH, so as to provide theoretical basis for clinical precision treatment in PH.